Pelaksanaan Sulh Dalam Islam: Kajian Terhadap Sistem Perundangan Syariah Di Malaysia - Hasnizam Hashim; Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Mohamad Aniq Aiman Alias; Norma Jusof; Zulfaqar Mamat; Norman Zakiyy Chow Jen-T'Chiang; Lukman Abdul Mutalib (Universiti Sains Islam Malaysia, 2026)
Non-Indexed Publication